Critique of everyday life - Lefebvre, Henri (London, 2008)
"The Critique of Everyday Life is perhaps the richest, most prescient work by one of the twentieth century's greatest philosophers. The trilogy which provided the philosophy behind the 1968 student revolution in France, it is considered to be the founding text of what we now know as cultural studies. Whether discussing sport, household gadgets, the countryside, surrealism, Charlie Chaplin or religion, Lefebvre always concentrates on the minutiae of lived experience in work and leisure, daydreams, and festivities. Denounced by both the right and left when it was first published in France in 1947, today this text is recognized as a path-breaking, radical, and hugely influential book. Volume 1 focuses on the various phenomena of daily life and considers them in new ways. "